Awareness, action and feedback in domestic energy use - Darby, S (2003)
The nature of gas and electricity and the methods of distribution, billing and payment all contribute to the 'invisibility' of much domestic energy consumption in industrial and post-industrial societies. For the householder, understanding how to invest and behave in ways that will give affordable comfort with minimum environmental impact involves making sense of a hidden set of processes. This poses a major challenge, one that a range of energy advice programmes is attempting to meet. The main focus to date has been on the actions taken as a result of advice, with little attention paid to teaching and learning processes or to context. This thesis explores formal and informal processes by which householders learn about their energy use in order to develop a theoretical framework. Constructivist learning theory guides the investigation and a variant of the 'conscious competence' model of learning is used as a starting point. The concept of'tacit knowledge' (foundational knowledge, usually acquired informally) is used in tracing the development of energy literacy. Empirical data come from householder surveys and from interviews of householders and advisers in five contrasting locations in the UK. Interpretation of this material demonstrates the construction of meaning through experience and interaction with others, and the potential role of the energy adviser as a trusted and knowledgeable person. The building of tacit knowledge is crucial to the development of energy literacy and the householder's ability to absorb and evaluate new information. Energy advisers need to be able to identify and develop existing knowledge, and to form effective networks with social welfare programmes. The need to build awareness by following up advice wherever possible is stressed. There also needs to be a supportive learning infrastructure that includes easily accessible feedback on consumption, and the availability of accurate information for those who are knowledgeable and confident enough to teach themselves.